EDOT-Functionalized Calix[4]pyrrole for the Electrochemical Sensing of Fluoride in Water - KOCA, ATIF (AMER CHEMICAL SOC, 2014)
A new calix[4]pyrrole compound bearing an electropolymerizable EDOT substituent (1) was synthesized, and its electrochemical behavior was investigated. The anion sensor ability of 1 was also studied in solution and in the solid state. Compound 1 interacts with halide ions selectively in solution, which illustrates its possible application as an anion sensor. To test possible practical applications, 1 and EDOT were electropolymerized on an ITO electrode, and this electrode was used as an effective fluoride anion sensor in the solid state.
Keywords: VERSATILE BUILDING-BLOCK; PENDANT CALIXPYRROLES; POLYMERIC EXTRACTANTS; ANION; ELECTROPOLYMERIZATION; POLY(3,4-ETHYLENEDIOXYTHIOPHENE); METHACRYLATE)S; RECOGNITION; DERIVATIVES; CORROSION